العلاقة بين نتيجة المتعلمين في مادة الصرف وقدرتهم في الإملاء في الصف الأول والثاني للمرحلة المتوسطة بمعهد دار الإخلاص منديلنج ناتل. - Amru Abdul Wadud; Slamet Riyadi; Arbonas Lubis (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research aims to know the picture of learners’ results in morphology and ability in dictation and the relationship between them among first-year students in the intermediate stage at Dar Al-Ikhlas Institute, Mandaling, Natl. The researcher used the quantitative method in the relational type with the statistical data analysis method using the relationship symbol (Product Moment). The result of the research indicates that the result of the learners in the morphology subject among the first-year students in the intermediate stage at the Dar Al-Ikhlas Institute, Mandaling Natal, is in the good category with a rate of 43, meaning 130 students, and their ability in dictation is in the good category, with a rate of 50%, meaning 15 students, and a relationship between the morphology result. The ability to boil dictation material has a correlation coefficient value of 797.0 at 69%, and the relationship is moderate with a positive direction.